A representação do usuário de maconha no cinema contracultural das décadas de 1960/1970 - Santos, Tiago Xavier dos (2016)
This thesis analyzes the representations about the marijuana user in countercultural movies of the 1960s and 1970. The paper first discusses the relationship that man establishes with the Cannabis Sativa plant and pioneering the United States in the prohibitionist policies on drugs . Later located the psychedelic movement and the film movement "New Hollywood" in the context of countercultural manifestations of the period. The paper also discusses the concept of image from the perspective of semiotics, on the relationship between cinema and history, the concept of representation of the historian Roger Chartier and considerations that must be made to make use of film as a source for historical research . Before analyzing the selected films, this work makes a historical contextualization of the marijuana user stigmatization process supported by the concept of Erving Goffman stigma, the concepts of Outsider and established Norbert Elias and the bypass notion of Howard Becker.